Where Does Education Pay Off in Sub-Saharan Africa? Evidence from Two Cities of the Republic of Congo - Mathias Kuepie; Christophe Jalil Nordman (Institute for the Study of Labor (IZA), 2015)
Using first-hand data from the 2009 Employment and Informal Sector Survey (EESIC) in the two largest cities of the Republic of Congo, Brazzaville and Pointe-Noire, we analyse the impact of education on labour market outcomes, and identify the segments where education pays off the most. Multivariate analyses of the risk of unemployment and sectoral choice indicate that young people face serious difficulties in the labour market: for most of them, their only choice is to remain unemployed or to join the informal sector. To measure the specific impact of schooling on earnings, we address issues related to sample selection and endogeneity of education in the earnings function. The results shed light on heterogeneity in the returns to schooling across the two main cities and institutional sectors. An important finding is that the informal sector does not systematically lag behind the formal sectors in terms of returns to education. We emphasize convex returns to education, meaning that the last years in secondary and tertiary schooling yield the highest returns, while those of primary education are generally lower. This convexity is also apparent in the informal sector, where education (albeit on another scale) again appears as an important determinant of earnings.
Keywords: J24; J31; O12; 330; informal sector; labour market participation; unemployment; returns to education; earnings functions; Republic of Congo